ASSOCIAÇÃO DO CAPITAL SOCIAL NA QUALIDADE DE VIDA RELACIONADA À SAÚDE BUCAL GESTANTES - Prates, Camila de Arruda Ribeiro (2023)
Social capital can be defined as the characteristics of social organization that facilitate cooperation for mutual benefit. Few studies have explored the influence of social capital on the oral health-related quality of life (OHRQoL) of pregnant women, so the objective of this cross-sectional study was to evaluate the association between individual social capital and the OHRQoL of pregnant women using the SUS. The sample consisted of 520 pregnant women treated at the public health service in the city of Santa Maria, Brazil, during the year 2022. Data collection included sociodemographic variables, individual social capital, health behaviors and oral health. The OHRQoL outcome was assessed using the OHIP-14 questionnaire. The results of the adjusted analysis revealed that the OHIP-14 total score was significantly associated with lower social support (RR: 1.21, 95% CI: 1.10-1.34). OHRQoL was also associated with other independent adjustment variables. Greater number of children (RR: 1.54; 95% CI: 1.43-1.66), lower level of education (RR: 1.18; 95% CI: 1.10-1.26) and lower income family (RR: 1.11; 95% CI: 1.04-1.18) were associated with worse OHRQOL in pregnant women. Furthermore, adulthood was a protective factor for worse OHRQoL (P< 0.05), compared to young/adolescent pregnant women. Alcohol consumption before pregnancy (RR: 1.09; 95% CI: 1.03-1.17) and seeking dental care due to pain (RR: 1.53; 95% CI: 1.44-1. 62) were also associated with worse OHRQoL. In relation to oral health, pregnant women with gingivitis (RR: 1.10; 95% CI: 1.03-1.17) and with greater severity of dental caries (RR: 1.24; 95% CI: 1.17- 1.32) had high OHIP-14 scores. The findings of the present study revealed that a lower level of social capital, assessed through social support, was associated with worse OHRQoL among pregnant women.